A INFLUÊNCIA DO TREINAMENTO RESISTIDO DE 20 SEMANAS NO NÍVEL DE DESENVOLVIMENTO MOTOR EM IDOSAS DA UNATI - UNIVERSIDADE ABERTA DA TERCEIRA IDADE - ESEFFEGO - Fabrício Galdino Magalhães; Daniel Eric Borges Faria; Matheus Henrique de Abreu Araújo; Jairo Teixeira Júnior (UniEVANGÉLICA, 2016)
Objective: To evaluate the influence of resistance training of 20 weeks in the motor development of active seniors women, from the Open University of the Third Age (UNATI/UEG). Methods: This is a non-controlled clinical trial conducted with adult seniors women, who did not present physical/mental limitations, with registration in UNATI/UEG. The evaluation of motor skills - body schema, temporal and spatial organization- of the Motor Scale for the Elderly (EMTI) contained in the motor evaluation Guide for Seniors, was performed before and after resistance training intervention during 20 weeks, three sessions weekly of50 minutes each one. The data analysis was performed using descriptive and inferential statistical level of significance p